2014
DOI: 10.2147/cia.s70307
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of raloxifene in postmenopausal Japanese women with osteoporosis or low bone mass (osteopenia)

Abstract: PurposeTo systematically review the literature describing the efficacy, effectiveness, and safety of raloxifene for postmenopausal Japanese women with osteoporosis or low bone mass (osteopenia).Materials and methodsMedline via PubMed and Embase was systematically searched using prespecified terms. Retrieved publications were screened and included if they described randomized controlled trials or observational studies of postmenopausal Japanese women with osteoporosis or osteopenia treated with raloxifene and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Raloxifene (RXF) is clinically used as a selective estrogen receptor modulator for the treatment of postmenopausal osteoporosis and estrogen-dependent breast cancer [ 1 , 2 ]. The absolute bioavailability RXF has been reported to be merely 2% following oral administration [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Raloxifene (RXF) is clinically used as a selective estrogen receptor modulator for the treatment of postmenopausal osteoporosis and estrogen-dependent breast cancer [ 1 , 2 ]. The absolute bioavailability RXF has been reported to be merely 2% following oral administration [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These drugs are very similar with respect to their chemical structures. Both are used for the treatment of postmenopausal osteoporosis [ 94 , 95 ]. As mentioned above, both possess an inhibitory effect on virus replication in which they can interact with viral proteases ( Table 2 ).…”
Section: Therapeutic Consequencesmentioning
confidence: 99%
“…A systemic review that included 15 studies reported a statistically significant increase in BMD of the lumbar spine, but not the hip region, a low incidence of vertebral fracture, decrease in markers of bone turnover, and improved hip structural geometry. [ 34 ] For lasofoxifene, another SERM, the randomized, double-blind, placebo-controlled study Postmenopausal Evaluation and Risk Reduction with Lasofoxifene (PEARL) clinical trial for vertebral fracture risk in postmenopausal women showed a 42% reduction compared with placebo ( P < 0.01), and 24% reductions in the absolute incidence of nonvertebral fracture. [ 35 ] In a 3-year randomized, double-blind, placebo-controlled study ( N = 7,492), bazedoxifene 20 mg and bazedoxifene 40 mg significantly ( P < 0.05) reduced the risk of new vertebral fractures by 42%, compared with placebo in postmenopausal women with osteoporosis.…”
Section: Calcitoninmentioning
confidence: 99%